Clinical And Epidemiological Features Of The Course Of Gastroduodenal Pathology Of The Drug-Using Population - Sodikova D.T; Rakhmatova M.M; Rahmonov I.A (Global Scientific Publishing, 2023)
It is assumed that drug addiction results in a variety of gastroduodenal lesions caused both by the direct toxic effects of opiates on the digestive organs and associated with disorders of the neuroendocrine homeostasis response and changes in immune and nonspecific protection systems, which leads to the formation of gastrointestinal disorders
Keywords: disorders; protection; systems